Influence of whitening gel on pulp chamber temperature rise by in-office bleaching technique - Sandro Cordeiro Loretto; Mylena Ranieri Libdy; Fabiola do Socorro da Rocha Ribeiro; Esther Marina França Braga; Karina Gama Kato Carneiro; Mário Honorato Silva e Souza Júnior
INTRODUCTION: Dental bleaching is a conservative method for the aesthetic restoration of stained teeth. However, whitening treatments are likely to cause adverse effects when not well planned and executed. OBJECTIVE: This study evaluated the influence of whitening gel on temperature rise in the pulp chamber, using the in-office photoactivated dental bleaching technique. MATERIAL AND METHOD: The root portion of an upper central human incisor was sectioned 3mm below the cemento-enamel junction. The root canal was enlarged to permit the insertion of the K-type thermocouple sensor (MT-401) into the pulp chamber, which was filled with thermal paste to facilitate the transfer of heat during bleaching. Three photosensitive whitening agents (35% hydrogen peroxide) were used: Whiteness HP (FGM), Whiteness HP Maxx (FGM) and Lase Peroxide Sensy (DMC). An LED photocuring light (Flash Lite - Discus Dental) was used to activate the whitening gels. Six bleaching cycles were performed on each group tested. The results were submitted to one-way ANOVA and LSD t-test (α<0.05). RESULT: The lowest mean temperature variation (ºC) was detected for Lase Peroxide Sensy (0.20), while the highest was recorded for Whiteness HP (1.50). CONCLUSION: The Whiteness HP and Whiteness HP Maxx whitening gels significantly affected the temperature rise in the pulp chamber during bleaching, and this variation was dependent on the type of whitening gel used.